(untitled) (Journal of Universal Science Research, 2023)
This article deals with the performance and fatigue of the body during the learning process in physical education lessons. The article reflects the capabilities of human biological nature, which serve as an indicator of his legal capacity. Proper organization of mental work and rest is an important condition for maintaining health, performance and successful mastery of academic disciplines.